Pooling biomarker data from different studies of disease risk, with a focus on endogenous hormones. - Key, T; Appleby, P; Allen, N; Reeves, G (2010)
Large numbers of observations are needed to provide adequate power in epidemiologic studies of biomarkers and cancer risk. However, there are currently few large mature studies with adequate numbers of cases with biospecimens available. Therefore, pooling biomarker measures from different studies is a valuable approach, enabling investigators to make robust estimates of risk and to examine associations in subgroups of the population. The ideal situation is to have standardized methods in all studies so that the biomarker data can be pooled in their original units. However, even when the studies do not have standardized methods, as with existing studies on hormones and cancer, a simple approach using study-specific quantiles or percentage increases can provide substantial information on the relationship of the biomarker with cancer risk.